2021
DOI: 10.22159/ajpcr.2021.v14i1.40049
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Analytical Methods for Determination of Type- Ii Antidiabetic Drugs in Pharmaceuticals and Biological Matrices

Abstract: Its a meglitinide analog is an oral symptom designed to common hour aldohexose excursions. Through not an antidiabetic, it acts in AN analogous manner by binding to antidiabetic receptor likewise on alternative one distinct receptor-» closure of adenosine triphosphate dependent K+ channel-» of depolarization-» internal secretion unharnesses. Repaglinide induces fast onset short-lasting internal secretion discharged. It is administered antero every main meal to stabilize postprandial hyperglycemia; the dose oug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…From the filtered solution, 1ml was pipetted out into a 10 ml volumetric flask and made upto 10ml with diluents 13 . Assay Method: Assay of the marketed formulation was carried out by injecting sample 14 corresponding to equivalent weight into HPLC system [15][16][17][18][19][20][21][22][23][24][25] Selection of Solvent: Metformin and Saxagliptin are marketed as combined dosage formulations. different solvents are used for the solubility of drugs, it was found that both the drugs are freely soluble in acetonitrile 15 .…”
Section: Methods Developmentmentioning
confidence: 99%
“…From the filtered solution, 1ml was pipetted out into a 10 ml volumetric flask and made upto 10ml with diluents 13 . Assay Method: Assay of the marketed formulation was carried out by injecting sample 14 corresponding to equivalent weight into HPLC system [15][16][17][18][19][20][21][22][23][24][25] Selection of Solvent: Metformin and Saxagliptin are marketed as combined dosage formulations. different solvents are used for the solubility of drugs, it was found that both the drugs are freely soluble in acetonitrile 15 .…”
Section: Methods Developmentmentioning
confidence: 99%